Piloting the Impact of Government Expenditure, Inflation, Unemployment, Trade Openness and Environmental Quality on Economic Growth: Empirical Insights from G7 Countries - Dahal, Arjun Kumar; Budhathoki, Prem Bahadur; Bhattarai, Ganesh; Pokhrel, Sagar (International Research Journal of MMC, 2025)
This study navigates the impact of government expenditure, unemployment, inflation rate, trade openness, and environmental quality in terms of carbon emissions on economic growth in G7 countries. It uses secondary data from seven-member countries of G7 spanning from 1990 to 2023. The unbalanced panel data were collected from various International Monetary Fund and World Bank reports. It covered 266 data points. The causal correlational research design was used. The positivist research philosophy, deductive reasoning, and quantitative analysis guided it. Some statistical tools like descriptive statistics, correlation analysis, Johnsen-Fisher and Kao residual panel cointegration test, Granger and Dumitrescu-Hurlin panel causality test, and Robust least square method were used to explore the impact of variables. The trade openness was not statistically significant in determining G7 countries' economic growth. The unemployment and inflation rates were individually significant in determining economic growth. One unit change in unemployment and inflation rate resulted in a 0.117 and 0.028 unit decrease in economic growth in G7 countries. Likewise, government expenditure had a positive and statistically significant (P=0.00) impact on economic growth. One unit increase in government expenditure results in a 0.044 increase in economic growth. Similarly, carbon emissions were also significant in determining economic growth. The carbon emissions and economic growth were simultaneously increased. The value of the R-squared was 0.653; it indicates that a nearly 65.3 percent variation in economic growth depended on unemployment, inflation rate, trade openness, government expenditure, and environmental quality regarding carbon emissions. To promote sustainable economic growth, policymakers in G7 nations should prioritize reducing unemployment and inflation while strategically boosting government spending and tackling carbon emissions, considering their substantial economic effects.